Development of striatal compartmentalization following pre- or postnatal dopamine depletion - Snyder-Keller, AM (J Neurosci, 1991)
Nigrostriatal dopamine (DA) projections terminate in distinct patches during the late prenatal and early postnatal period in the rat. During the first postnatal week, patches of DA fibers overlap with clusters of striatal neurons that share several identified characteristics. The early segregation of striatal cell types into either these patches or the surrounding matrix becomes a permanent organizational feature of the striatum. In order to determine whether the heterogeneous distribution of DA influences the formation of cellular patches, the developmental organization of chemically identifiable cell types was examined in normal rats and in rats DA depleted as infants (0 or 3 d) or in utero (embryonic days 17–18). During the first postnatal week, corresponding patches of DA afferents and substance P (SP)- immunoreactive neurons existed in the striatum of normal animals, and AChE-positive zones overlapped these patches in the lateral striatum. Injection of 6-hydroxydopamine into the lateral ventricles of fetal or infant rats produced a dramatic loss of striatal DA terminals. Neither the patchy distribution of SP-immunoreactive neurons nor the distinctive pattern of AChE staining present during the first 2 postnatal weeks was disrupted. During the third postnatal week, cells immunoreactive for leu-enkephalin or calbindin-D28k were confined to the matrix compartment, and this compartmentalization was also not noticeably changed by pre- or postnatal DA depletion. In adult animals, overlapping patches of leu-enkephalin- and SP-immunoreactive fibers were observed, regardless of whether any DA terminals remained. Thus, the basic organization of the striatal patch and matrix compartments develops normally in the absence of DA innervation through much of the formative period. Although these observations do not completely dismiss the possibility that the first DA afferents to appear in the striatal primordia influence contracted striatal cells to develop the patch phenotype, they suggest that the patchy distribution of DA afferents may be secondary to the early clustering of striatal neurons forming the patch compartment.